Breakthrough infections due to SARS-CoV-2 Delta variant: relation to humoral and cellular vaccine responses - Buscot, Matthieu; Cremoni, Marion; Graça, Daisy; Brglez, Vesna; Courjon, Johan; Allouche, Jonathan; Teisseyre, Maxime; Boyer, Laurent; Barrière, Jérôme; Chamorey, Emmanuel; Carles, Michel; Seitz-Polski, Barbara (Frontiers in Immunology, 2023)
COVID-19 vaccines are expected to provide effective protection. However, emerging strains can cause breakthrough infection in vaccinated individuals. The immune response of vaccinated individuals who have experienced breakthrough infection is still poorly understood. Here, we studied the humoral and cellular immune responses of fully vaccinated individuals who subsequently experienced breakthrough infection due to the Delta variant of SARS-CoV-2 and correlated them with the severity of the disease. In this study, an effective humoral response alone was not sufficient to induce effective immune protection against severe breakthrough infection, which also required effective cell-mediated immunity to SARS-CoV-2. Patients who did not require oxygen had significantly higher specific (p=0.021) and nonspecific (p=0.004) cellular responses to SARS-CoV-2 at the onset of infection than those who progressed to a severe form. Knowing both humoral and cellular immune response could allow to adapt preventive strategy, by better selecting patients who would benefit from additional vaccine boosters.